Development of pretreatment techniques for high productivity gaharu extraction - Zuraidah, Mohd Ali (2010)
Gaharu or Agarwood is a resinous wood from aquilaria species, naturally grown in tropical forest. It is of high demand from various industries for it contains therapheutical essential oil commonly used in cosmetic industry, religious ceremony and traditional medicine. Due to its high demand and scarce in the forest, gaharu oil is highly priced. As of early 2010, gaharu oil in Malaysia is valued at RM420 per tola (12g). Hence, it is of great importance for an efficient method of extracting the oil to be developed. The conventional method of extraction currently practiced in the industry requires very long hours and produces low oil yield. The present study focused on developing pretreatment steps of conditioning the gaharu wood prior to extraction in order to enhance the extraction process. Preliminary experimental work showed that all pretreatment methods of gaharu wood examined in the study strongly influenced the oil yield during extraction. Four types of pretreatment methods were examined, namely soaking (typically used in industry), ultrasonication, enzymatic and combination of ultrasonication and enzymatic. From the study, combination of ultrasonication and enzymatic pretreatment method was found to give the highest oil yield (0.1232%), followed by ultrasonication (0.1134%), enzymatic (0.1088%) and soaking (0.0734%) respectively. In comparison to untreated sample, an improvement of 53.57% was achieved in the extraction of sample pretreated with combination of ultrasound and enzymatic. On the other hand, soaking technique improved the oil yield by 28.32%. In general, hydro distillation performed better than steam distillation for extraction of gaharu oil, with extraction yield increased up to 35% due to the fact that hydro distillation provides continuous water phase within the solid structure as compared to steam distillation where not all solid surfaces are in contact with the passing steam. At optimum operating conditions, the highest oil yield from combination of ultrasonic and enzymatic pretreatment method was 0.1692%, at 9 hours pretreatment time, 1:16w/v of sample to water ratio and 1.5:100v/w of enzyme to substrate ratio. Calculation of extraction rate constant (Ko) showed that Ko for the combination of ultrasonic and enzymatic pretreated sample was greater than the value for the conventional (soaking) pretreated sample, with value of 0.45 and 0.25 respectively. The increased of Ko value indicates greater driving force of mass transfer at the solid-liquid interface.